First high resolution study of the interacting ν8+ν10, ν6+ν10, ν6+ν7 bands and re-analysis of the ν7+ν8 band of trans-d2-ethylene; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 184 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Zyatkova (Ziatkova) A. G. Anastasiya Georgievna; Sydow С.; Maul C.; Bauerecker (Bauerekker) Z. (S.) H. Zigurd (Sigurd) Hermann (2016, 2016)
Title screen